Hemodynamic effect of pimobendan following intramuscular and intravenous administration in healthy dogs: A pilot study - Enokizono, Masayuki; Mandour, Ahmed S.; Komeda, Syunta; Goya, Seijirow; Takeuchi, Aki; Katoh, Konosuke; Yairo, Akira; Yilmaz, Zeki; Shimada, Kazumi; Tanaka, Ryou (Frontiers in Veterinary Science, 2022)
Background: Pimobendan is widely used for the treatment of dogs with heart failure via the oral route. A new injectable form of pimobendan is now available and its potential usefulness via intravenous route has been recently demonstrated in dogs. However, the cardiovascular effects of intramuscular (IM) administration of injectable pimobendan have not been investigated yet. Hypothesis: IM administration of pimobendan may have the same hemodynamic effect as the IV route. Methods: Six healthy Beagle dogs underwent a placebo-controlled double-blind crossover study. The early cardiovascular effects after a single dose of IM and IV injections of pimobendan (0.2 ml/kg; Pimo IM and Pimo IV, respectively) were compared to the same volume of IM placebo (Saline IM) in anesthetized dogs. Clinical (heart rate HR and blood pressure BP) and echocardiographic hemodynamic parameters (left ventricular LV inflow waveforms of diastolic early wave eV, atrial systolic wave aV, diastolic early mitral ring velocity e', peak velocity pV, stroke volume SV, cardiac output CO, and systemic vascular resistance SVR) were monitored with 15 min intervals for 120 min. Results: Diastolic BP decreased significantly at 30 min in Pimo IM compared to Saline IM. Mean eV and CO values significantly increased from 75 min, e' from 60 min, pV from 75 min, and SV from 15 min to 120 min, whereas SVR significantly decreased at 30-60 min in Pimo IM compared to those of Saline IM (P < 0.05). Compared with the Pimo IV, eV and pV were significantly lower at 30 – 60 min (P < 0.05) while SV was significantly higher at 90-105 min in Pimo IM (P < 0.05). Other hemodynamic parameters (BP, HR, SVR, CO, e' and E/e’) did not significantly change between Pimo IM and IV. Conclusions: The hemodynamic effect of pimobendan following IM and IV injection was described. Our results suggested that IM administration of pimobendan is equally comparable and possibly interchangeable with IV administration. This warrant further studies to investigate the clinical effectiveness of IM pimobendan in treating dogs with congestive heart failure or in heart failure cases unable to receive IV or oral administration.